THE INFLUENCE OF LEADERSHIP STYLE AND WORK STRESS ON EMPLOYEE PERFORMANCE IN HUTA BAYU RAJA SUB-DISTRICT OFFICE - Jopinus Saragih (CV. Radja Publika, 2023)
This study aims to see the influence of Leadership Style and Job Stress on Employee Performance both partially and simultaneously at the Huta Bayu Raja District Office. The type of research used is quantitative. The population in this study were employees of the Huta Bayu Raja sub-district office, totaling 31 people and determining the number of samples in this study by making the population a sample, but not including the head of the sub-district, because the subject of influence in this study was the head of the sub-district. So that the sample of this study amounted to 30 respondents. The data source for this research is primary data using a research instrument in the form of a questionnaire. The data collection method used is survey research. This study uses multiple linear regression analysis for statistical analysis and the regression model has been tested first in the classical assumption test. The results of the study stated that the partial test showed that Leadership Style had a significant positive effect on Employee Performance in the Huta Bayu Raja District Office, and the partial test showed that Job Stress had a significant negative effect on Employee Performance in the Huta Bayu Raja District Office. Taken together, Leadership Style and Work Stress have a significant effect on Employee Performance at the Huta Bayu Raja District Office. In the tcount test 2.923 > 1.703 ttable, with a significant value of 0.007 <0.05 it was stated that there was a significant influence between leadership style on employee performance at the Huta Bayu Raja District Office. In the tcount test -0.773 <1.703 ttable, with a significant value of 0.446 > 0.05, it was stated that there was no effect of work stress on employee performance at the Huta Bayu Raja District Office. In the fcount test 4.461 > 3.32ftable, with a significant value of 0.021 <0.05 it was stated that simultaneously there was a significant influence between leadership style and work stress on employee performance in the Huta Bayu Raja District Office. The leadership style used in this study is a democratic leadership style, where the sub-district leader always involves employees in every decision-making deliberation as well as an unselfish and exemplary leader. 05 stated that jointly there is a significant influence between leadership style and work stress on employee performance in the Huta Bayu Raja District Office. The leadership style used in this study is a democratic leadership style, where the sub-district leader always involves employees in every decision-making deliberation as well as an unselfish and exemplary leader. 05 stated that jointly there is a significant influence between leadership style and work stress on employee performance in the Huta Bayu Raja District Office. The leadership style used in this study is a democratic leadership style, where the sub-district leader always involves employees in every decision-making deliberation as well as an unselfish and exemplary leader.